PENGARUH KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH DI VARIA STORE - TANGERANG - ., AHMAD (Universitas Islam Syekh-Yusuf, 2018)
This research was done in order to analyze the variable effect (X1) namely Quality of Product to variable (Y) namely Purchasing Decision, variable effect (X2) namely Brand Image to variable (Y) namely Purchasing Decision, and variable effect (X1) namely Quality of Product and variable (X2) namely Brand Image to variable (Y) namely Purchasing Decision. This research was done by using a Survey Method. The population in this research were the use cosmetic produc Wardah in Varia Store Tangerang, taking of sample was done by Incidental Sampling technique, and the amount is 100 respondents. Whereas the data analysis was done by associative analysis, Validity test, Reability test,Hypotesist test, simple regression analysis, multiple regression analysis, simple correlation analysis, multiple correlation analysisand coefficient determination (RÂ²). Based on the analysis data which was done in this research, can be concluded that variable (X1) which is Quality of Product give an positive influence and significant impact on variable (Y)which is Purchasing Decision for Variable 89,0% effect (X2) which is Brand Image give an positive influence and significant impact on variable (Y)which is Purchasing Decision 90,0%. And Variable effect(X1) which is Quality of Product and variable (X2) which is Brand Image found positive and significant impact on variable (Y)which is Purchasing Decision for 89,0%. Value of F-count which is 9,179 is more than value of F-table which is 3,090. The result is Ho refused and Ha accepted. Whereas the residual is influenced by the other variable which didnâ€™t researched in this research.